Discovery of potent and selective CDK8 inhibitors through FBDD approach. Issue 18 (15th September 2017) - Han, Xingchun; Jiang, Min; Zhou, Chengang; Zhou, Zheng; Xu, Zhiheng; Wang, Lisha; Mayweg, Alexander V.; Niu, Rui; Jin, Tai-Guang; Yang, Song
Graphical abstract: Abstract: A fragment library screen was carried out to identify starting points for novel CDK8 inhibitors. Optimization of a fragment hit guided by co-crystal structures led to identification of a novel series of potent CDK8 inhibitors which are highly ligand efficient, kinase selective and cellular active. Compound16 was progressed to a mouse pharmacokinetic study and showed good oral bioavailability.